MEDIATION AS A CATEGORY OF HUMANISTICORIENTED PEDAGOGY - Bieszczad, Bogusław; Kozłowska, Karina; Łopatkiewicz, Agata (European Scientific Journal, ESJ, 2014)
This paper analyzes the category of mediation from the point of view of humanisticoriented pedagogy. Mediation is discussed first in its presumably most popular context, that is, in the context of legal procedures, where Polish law is taken as an illustrative material. Against this background, the main functions and principles of legal concept of mediation are presented. Further investigations are devoted to the characterization of humanistic-oriented pedagogy, with emphasis on the main categories of this type of pedagogical inquiry. The very notion of category is also focused on. Finally, the research question concerning the understanding of mediation as a category of humanistic-oriented pedagogy is discussed. It is argued that certain important values underlying the legal concept of mediation are present in the research in pedagogy, but in the latter context, the category of mediation adopts a much broader meaning, for its elements are present in every stage of human development.